Techno-economic Analysis of a Smart-grid Hybrid Renewable Energy System for Brisbane of Australia - Shezan, S.; Das, Narottam; Mahmudul, H. (2017)
© 2017 The Authors. The immense percentages of people of the world are living mostly in the decentralized, rural and remote areas those are geographically secluded from the grid connection. Power distribution and continuous fuel transportation to produce the electrical energy for these areas pretences a great challenge. A smart-grid hybrid energy system has been designed and simulated to support a small community considering an average load demand of 34 kWh/d and peak load of 4.6 kW. The total simulation and optimization process of the hybrid energy system have been done by HOMER Software with the meteorological data. The simulation results ensure that the proposed system is economically and environmentally feasible. The results show that Net Present Cost (NPC) and CO 2 emission can be reduced about 29.65% per year compared to the conventional power plants. The NPC of the optimized system has been found about US$ 33,310.00 having the Cost of Energy (COE) about US$ 0.209/kWh. This analysed hybrid system will be applicable for similar meteorological and environmental conditions. This analysed hybrid system will be applicable for similar meteorological and environmental conditions. The urban area, including the central business district, are partially elevated by spurs of the Herbert Taylor Range, such as the summit of Mount Coot-tha, reaching up to 300 meters (980 ft) and the smaller Enoggera Hill, Brisbane, Australia. Using renewable energy resources in off grid hybrid energy system might be a solution of this issue. Moreover, high cost of renewable energy systems has led to its slow adoption in many countries. Hence, it is vital to select an appropriate size of the system in order to reduce the cost and excess energy produced as well as to maximize the available resources. Reduction of some greenhouse gasses as well as reduction of per unit cost according to the market price are main contribution of this research. The analysed hybrid solar-wind-diesel renewable energy system will be the most feasible and environment friendly in comparison with other traditional or conventional energysources in terms of reliability and cost effectiveness.